Authoritarian Africa repression, resistance, and the power of ideas - Cheeseman, Nic 1979-; Fisher, Jonathan 1985- (Oxford University Press, 2021)
"A higher education history textbook on the history of authoritarianism in Africa"--
Literaturangaben
Erschienen in 2019
Keywords: Unterdrückung; Autorität; Kulturkonflikt; Widerstand; Afrika; Authoritarianism / Africa; Democratization / Africa; Afrika / Staat / Herrschaftsform / Regierungssystem / Autoritäre Herrschaft / Autoritarismus / Bestimmungsfaktoren / Geschichtlicher Überblick; Africa / State / Rule systems / Government systems / Authoritarian rule / Authoritarianism / Determinants / Historical surveys; Africa / Politics and government / 1960-